MEDICINAL VALUES OF PUTRANJIVA ROXBURGHII-A REVIEW - B., Supriya; Vijayakumar, Keerthana; Subramanian, Nambirajan; Mahendradas, Dharmendira Kumar (International Journal of Current Pharmaceutical Research, 2017)
The evolving economic concerns and the depletion of natural sources motivate the researchers to look for various alternatives. We started utilizing the bio resources like bio-diesel that is substituted over Petro-diesel. As the needs increasing day by day, it is our responsibility to not to deplete all the resources available now and hence not making the future generation in a great risk. So the idea is to find new sources that we can utilize and to also try to utilize the natural resources around us in a useful manner. In a recent trend, there are more technologies available for utilizing bio-resources in an effective manner. One such kind of bio-resource we can utilize is Putranjiva roxburghii. The ultimate aim of this review paper is to create a limelight on the medicinal values of Putranjiva plant. This current study explains the research works done so far with Putranjiva plant in a detailed manner and also to create awareness on growing Putranjiva plant all over the world. The plant material can be utilized as Anti-oxidant, febrifuge and for anti-inflammatory activities, as biofuel, as an herbal preservative, as an Antioxidant agent and as Trypsin inhibitor. The commercial, as well as medicinal values of Putranjiva, are so attractive, that encourages the authors to write a review over this excellent plant material.